2022
DOI: 10.1101/2022.04.10.22273673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Brain Reacting to COVID-19: Analysis of the Cerebrospinal Fluid and Serum Proteome,Transcriptome and Inflammatory Proteins

Abstract: Patients with COVID-19 can have a variety of neurological symptoms, but the pathomechanism of CNS involvement in COVD-19 remains unclear. While routine cerebrospinal fluid (CSF) analyses in patients with neurological manifestations of COVID-19 generally show no or only mild inflammation, more detailed data on inflammatory mediators in the CSF of patients with COVID-19 are scarce. Here, we used mass spectrometry to study the proteome, Enzym-linkend immunoassays, semiquantitative cytokine arrays, autoantibody s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…However, we did not see a marked increase in T cell numbers or additional microglial populations as previous studies ( Supplementary Figure 3 c ) 8,14,87,88 probably due to our control group with also multi-organ failure, superinfection and to some degree neurodegenerative diseases similar to the COVID-19 groups ( Supplementary Table 1 ). The described IFN response in our study is probably not SARS-CoV-2-specific and not only seen in severe COVID-19 as similar alterations of neurons and oligodendrocytes were previously described in CNS viral infections caused by the West Nile virus (WNV) 31 and - in the CSF - by Herpes virus (HSV; Figure 3 ) 10 . Interestingly, during COVID-19 we found a tendency to reduced glutamatergic neurons (not significant in our testing) but we found a net reduction of OPALIN+ oligodendrocytes, a finding previously reported in demyelinating lesions and ‘normal appearing white matter’ in multiple sclerosis (MS) 89 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, we did not see a marked increase in T cell numbers or additional microglial populations as previous studies ( Supplementary Figure 3 c ) 8,14,87,88 probably due to our control group with also multi-organ failure, superinfection and to some degree neurodegenerative diseases similar to the COVID-19 groups ( Supplementary Table 1 ). The described IFN response in our study is probably not SARS-CoV-2-specific and not only seen in severe COVID-19 as similar alterations of neurons and oligodendrocytes were previously described in CNS viral infections caused by the West Nile virus (WNV) 31 and - in the CSF - by Herpes virus (HSV; Figure 3 ) 10 . Interestingly, during COVID-19 we found a tendency to reduced glutamatergic neurons (not significant in our testing) but we found a net reduction of OPALIN+ oligodendrocytes, a finding previously reported in demyelinating lesions and ‘normal appearing white matter’ in multiple sclerosis (MS) 89 .…”
Section: Discussionsupporting
confidence: 80%
“…This part of the study was approved by the local ethics committees at Charité (EA1/76/20). And these samples are also included in a separate CSF study 10 .…”
Section: Csf Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, our data suggests that it is not COVID-19 itself, but rather the severity of COVID-19 respiratory disease requiring ICU treatment and concomitant renal dysfunction that leads to elevated sNfL levels, and both, sNfL and creatinine, are associated with poor clinical prognosis. Other studies on the correlation of Neuro lament light Chain levels and COVID- 19 All data is available by request to the corresponding author.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these studies did not consider factors in uencing sNfL levels, such as renal dysfunction, hypoxia or body mass index (14). The exact pathomechanisms leading to COVID-19 causing neurological symptoms are still speculative, but the consequences of critical illness and hypoxia, hypercoagulopathy, para-and post-infectious in ammation as well as the possible direct viral nerve infection may play a role (2,(15)(16)(17)(18)(19). In a post-mortem study, myositis-like histopathology was found in COVID-19 patients, indirectly suggesting presumed retrograde neuroaxonal injury from muscle pathology, which is more prevalent in COVID-19 ICU patients than previously thought before (20).…”
mentioning
confidence: 99%